2014
DOI: 10.1515/ejnm-2013-0018
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of the size and charge distribution of sodium chloride particles generated by an Aeroneb Pro® pharmaceutical nebulizer

Abstract: The charge distribution of aerosol is an important factor for accurate prediction of aerosol behavior as it influences particle transport, settling, deposition, and coagulation. In the production of aerosol for pulmonary drug delivery, charging of aerosol particles is influenced by both the generation method and chemical properties of the drug. Electrostatic charging of add-on devices such as plastic spacers and holding chambers will reduce the delivery to the lung, while charged particles can also enhance dep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…Aerosol charge distribution from active vibrating‐mesh nebulizers has recently been investigated with (TDMA). The results showed that the levels of negatively charged droplets from nebulization of normal saline are superior to that of positively charged particles and that the fraction of charged particles is greater for those below 200 nm in size . Although charge distributions can greatly differ with different nebulizer configurations and formulation compositions, TDMA was successfully used to determine submicron particle charge, which can influence patterns of drug deposition in the lungs.…”
Section: Established Nebulizersmentioning
confidence: 99%
“…Aerosol charge distribution from active vibrating‐mesh nebulizers has recently been investigated with (TDMA). The results showed that the levels of negatively charged droplets from nebulization of normal saline are superior to that of positively charged particles and that the fraction of charged particles is greater for those below 200 nm in size . Although charge distributions can greatly differ with different nebulizer configurations and formulation compositions, TDMA was successfully used to determine submicron particle charge, which can influence patterns of drug deposition in the lungs.…”
Section: Established Nebulizersmentioning
confidence: 99%
“…Instead, in this study, we dispense with an additional charging unit and sample only the naturally positive-charged aerosol fraction. As a quantitative measure of the charging state of a naturally charged aerosol we adopt the size and charge distributions measured in the range of d p = 20 nm to 400 nm with a NaCl aerosol [ 33 ], which we consider as a model system for aerosol charge distributions generated by a nebulizer. We assume that this non-equilibrium charge distribution can describe not only NaCl but also other nebulized aerosols with sufficient accuracy even if, in general, the charge distribution may be dependent on the specific aerosol nebulizer configuration and the chemical composition of the nebulized solution.…”
Section: Aerosol Particle Sizing Using the Micro Electro Mechanical System-differential Mobility Particle Sizer (Mems-dmps)mentioning
confidence: 99%
“…Measured fractions of n -times ( n = 1, 2, 3, 4, 5, 6) positive-charged particles with diameters of d p = 20 nm, 30 nm, 70 nm, 100 nm, 200 nm, and 400 nm are given in reference [ 33 ] for a NaCl aerosol generated by a nebuliser ( Table A1 ). Values for n = 5, 6 are determined by extrapolation.…”
Section: Table A1mentioning
confidence: 99%